Global modern art - Richardson, Margaret (Art historian), author. aut Link Link
1 online resource
Keywords: "This accessible, foundational volume explores how modern art developed around the world by comparing contexts and artistic production in Europe, the Americas, Asia, and Africa from circa 1850 through the 1960s. To provide a broader, more comprehensive view of modern art, chronological and thematic approaches will be used and selections from all regions of the world will be included-from Africa, Asia, the Americas, as well as Europe. Each section begins with an overview of the region leading into more detailed case studies of specific countries' historical contexts, including their cultural and aesthetic values and the ways in which cultures have interacted with regional neighbours and outside forces. Examples of specific artists and groups will be discussed for each country and will illuminate themes that illustrate cultural distinctions and connect to broader modern trends traced throughout the text. This book will be of interest to students and scholars working in art history, modernism, globalization and decolonization"-- Provided by publisher.